2017
DOI: 10.1007/s12640-017-9841-7
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the PAC1 Receptor Expression in the Basal Ganglia of MPTP-Induced Parkinsonian Macaque Monkeys

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a well-known neuropeptide with strong neurotrophic and neuroprotective effects. PACAP exerts its protective actions via three G protein-coupled receptors: the specific Pac1 receptor (Pac1R) and the Vpac1/Vpac2 receptors, the neuroprotective effects being mainly mediated by the Pac1R. The protective role of PACAP in models of Parkinson's disease and other neurodegenerative diseases is now well-established in both in vitro and in vivo studies. PACAP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…In a recent study, the decrease in PAC1 receptor expression was found in structures undergoing degeneration in MPTP-induced macaque model of Parkinson's disease (Feher et al 2018). While there was no change in the receptor expression in an area not directly linked to Parkinson's disease (somatosensory cortex), marked reductions were observed in the striatum, external and internal pallidum, and putamen (Feher et al 2018). The strong, specific decrease of PACAP receptor immunosignal in the basal ganglia of parkinsonian macaque monkey brains suggests that the PACAP/PAC1R system may play an important role in the development/progression of this age-related disease (Feher et al 2018).…”
Section: Pacap Levels Change In Agingmentioning
confidence: 94%
See 2 more Smart Citations
“…In a recent study, the decrease in PAC1 receptor expression was found in structures undergoing degeneration in MPTP-induced macaque model of Parkinson's disease (Feher et al 2018). While there was no change in the receptor expression in an area not directly linked to Parkinson's disease (somatosensory cortex), marked reductions were observed in the striatum, external and internal pallidum, and putamen (Feher et al 2018). The strong, specific decrease of PACAP receptor immunosignal in the basal ganglia of parkinsonian macaque monkey brains suggests that the PACAP/PAC1R system may play an important role in the development/progression of this age-related disease (Feher et al 2018).…”
Section: Pacap Levels Change In Agingmentioning
confidence: 94%
“…In a recent study, the decrease in PAC1 receptor expression was found in structures undergoing degeneration in MPTP-induced macaque model of Parkinson's disease (Feher et al 2018). While there was no change in the receptor expression in an area not directly linked to Parkinson's disease (somatosensory cortex), marked reductions were observed in the striatum, external and internal pallidum, and putamen (Feher et al 2018).…”
Section: Pacap Levels Change In Agingmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, recent results obtained in different animal models of PD showed the dysregulation of PACAP and its receptors in brain areas related to cognition. A specific reduction of PAC1 receptor was reported in the basal ganglia of MPTP-induced parkinsonian macaques (Feher et al, 2018). Likewise, PACAP-knockout mice were shown to be more vulnerable to paraquat (a pesticide that increases the risk of PD) than wild-type (Watson et al, 2013).…”
Section: Parkinson's Diseasementioning
confidence: 98%
“…The neuroprotective effects of PACAP have been shown in several different cell types in vitro against various toxic agents, such as oxidative stress, glutamate or 6-hydroxydopamine [14][15][16]. In vivo descriptions have also proven that PACAP is protective in global and focal cerebral ischemia [15,17,18], traumatic brain injury and neurodegenerative diseases [19,20].…”
Section: Text: Introductionmentioning
confidence: 99%